Control of grid connected inverter system for sinus oidal current injection with improved performance - Simeen. S. Mujawar.,; Prof. Mrs. G. M. Karve , (International Journal of Innovations in Engineering Research and Technology, 2021)
The control strategy for the grid connected inverter (GCI) duringabnormal conditions like voltage sag, swelland line to ground fault has been presented. The strategy adoptedhere operates even during faulty conditions,unlike the conventional controller which fails to operate during faulty conditions. The Multi-Reference Frame(MRF) PI Controller is used for this purpose. In order to study the Dynamic Performance of the system, it issimulated in Matlab Simulink environment. The overall system issimulated for normal condition that iswithout the presence of fault, and with the presence of fault.The performance is also studied during abnormalconditions of the grid and its results are analyzed. The simulation results exhibit improved performance of thesystem during normal as well as abnormal conditions.